Edukasi Manajemen Bencana Gempa Bumi di Yayasan Pendidikan SMP Nur Adia Tanjung Selamat Deli Serdang - Meutia Nanda; Hilwa Irvi Adzkia; Ira Sulastri Pasaribu; Qory Adinda Siregar; Siti Adelia Arsita; Widya Fadhillah (Pusat Riset dan Inovasi Nasional, 2026)
An earthquake occurs when energy is suddenly released within the earth’s layers, potentially causing loss of life and environmental damage. One factor contributing to the high impact of earthquakes is the lack of student understanding and inadequate education on disaster preparedness. This study aimed to assess earthquake disaster management education at the Nur Adia Junior High School Education Foundation, Tanjung Selamat, Deli Serdang. A quantitative pre-experimental design with a one-group pretest and posttest was applied, involving 63 eighth-grade students. Data were collected through questionnaires to measure students’ knowledge before and after the educational intervention on earthquake disaster management. The results indicated that before the education, 69.8% of students rarely received information about earthquake causes, 61.9% had never participated in school earthquake evacuation simulations, and 55.5% had never practiced evacuation drills. After the educational intervention, knowledge improved, with 66.6% of students reporting that the program significantly increased their understanding of earthquakes. Statistical analysis showed a significant difference between pretest and posttest scores (Sig. 2-tailed = 0.000 < 0.05), confirming the effectiveness of the intervention. The study concluded that education on earthquake disaster management can enhance students’ knowledge and preparedness. It is recommended that schools implement regular educational programs and disaster simulation exercises to cultivate students’ readiness and promote a culture of disaster preparedness within the school environment.